Evaluating the impact of a walking program in a disadvantaged area: using the RE-AIM framework by mixed methods - Camila Tiome Baba; Isabela Martins Oliveira; Adriele Evelyn Ferreira Silva; Leonardo Moreira Vieira; Natalia Caroline Cerri; Alex Antonio Florindo; Grace Angélica de Oliveira Gomes (BMC, 2017)
Abstract Background The positive health impact of physical activity (PA) is well known, yet a large proportion of the world's population remains sedentary. General PA programs are common as health promotion initiatives. However, effectiveness evaluations of such PA programs on individual and organizational aspects, which could inform the decision-making process of public health bodies are still lacking, particularly in the most socially disadvantaged areas, where health promotion schemes are particularly needed. The aim of this study was to assess the effectiveness of a Guided Walking Program in a high social vulnerability context. Methods A quasi-experimental, mixed methods study was conducted. The program had a duration of 6 months and a 6-month follow-up period after the intervention. Session frequency was five times a week, where sessions consisted of supervised PA combined with educational sessions. The Reach, Effectiveness, Adoption, Implementation and Maintenance (RE-AIM) framework was followed to assess the program. The International Physical Activity Questionnaire (IPAQ) and accelerometers were used to measure levels of PA. Focus groups were conducted to gain a comprehensive insight on the implementation domain. Results Most subjects in the intervention (IG) (n = 74) and control (CG) (n = 74) groups were female (IG:90.5%; CG:95.9%), aged 18-49 years (IG:44.6%; CG:43.2%), received less than 1 minimum wage (IG:74.3%; CG:83.7%) and had 0-4 years of formal education (IG:52.1%; CG:46.1%). The reach of the intervention was 0.3%. The IG showed increased levels of PA at post-intervention and 6-month follow-up. However, the difference between groups was not statistically significant. Adoption data revealed that 89.5% of the professionals in the Primary Health Care Center (health center) team perceived the benefits of the program for the population. The program was independently promoted by the health center team for a further 4 months post-intervention. The qualitative data revealed that the program was discontinued due to participants' low adherence and human resource limitations in the unit's operational dynamics. Conclusions A health promotion intervention in a socially deprived setting faces challenges but can be effective and feasible to implement. The present study informs the development of future health promotion initiatives in this context. Trial registration NCT02857127 . Registered: 30 July 2016 (retrospectively registered).